THE RELATIONSHIP BETWEEN CONSUMER BEHAVIOR AND THE HIGH RATE OF COD PAYMENT DEFAULT IN E-COMMERCE AMONG THE PEOPLE OF SURABAYA - Prameswari, Manda Destara; Lating, Ade Irma Suryani (International Journal of Accounting Innovation, 2025)
Objective:This study aims to examine the relationship between consumer behavior and the high rate of payment default in Cash on Delivery (COD) transactions within e-commerce in Surabaya. Method: A descriptive qualitative approach was employed, with data collected through interviews and direct observations involving consumers, business owners, and couriers in Surabaya. Results: The results indicate that consumer behavior significantly influences the prevalence of COD payment defaults. The main factors contributing to these defaults include impulsive buying behavior, low levels of digital and financial literacy, a lack of transactional responsibility, and the absence of strict sanctions within e-commerce systems. Novelty: This study is expected to serve as a reference for business actors and e-commerce platforms in formulating strategies to enhance consumer literacy and improve risk management policies related to COD transactions.